Media Attention and Choice of Major: Evidence from Anti-Doctor Violence in China - Shiyu Bo; Y. Joy Chen; Yan Song; Sen Zhou (Global Labor Organization (GLO), 2018)
We study the relationship between media attention and major choices by evaluating how newspaper reports on violence against doctors in China deter students from choosing medicine as their college majors. We collect relevant articles from over 1,200 newspapers and combine them with an administrative dataset including the universe of students admitted to Chinese colleges from 2005 to 2011. An additional article on violence against doctors leads to a 0.5 percent decrease in the number of students choosing medicine majors, especially majors training physicians and nurses. Students attending elite colleges and with above-median test scores are more responsive to media attention. Consequently, it significantly reduces the quality of admitted medical students, measured by their entrance exam performance.
Keywords: 330; Media attention; College majors; Occupational choice; Health care